2007
DOI: 10.1264/jsme2.22.336
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Mercury-Resistant Marine Bacteria for Detoxification of Chemicals of Environmental Concern

Abstract: The hypothesis that mercury-resistant bacteria exposed to polluted environments such as coastal areas can tolerate, detoxify, or biotransform a variety of other toxicants was examined. Several mercury-resistant marine bacteria from the coastal waters of India were evaluated for their ability to biotransform the heavy metals mercury, cadmium and lead as well as xenobiotics like polychlorinated biphenyls and tributyltin. These salt-tolerant bacteria removed mercury by means of volatilization and were successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…As early as the 1970s, Singbal et al reported 26–187 ng/l mercury in regions off Goa. Subsequently, after three decades, De et al observed 152–456 ng/l mercury in Mormugao, Goa. Lead concentrations ranging from 4.5–46.5 µg/g have been recorded in sediments of the Mandovi Estuary , whereas mangrove sediments along the Chapora and Mandovi Rivers revealed 7.9–50.5 µg/g of lead .…”
Section: Discussionmentioning
confidence: 99%
“…As early as the 1970s, Singbal et al reported 26–187 ng/l mercury in regions off Goa. Subsequently, after three decades, De et al observed 152–456 ng/l mercury in Mormugao, Goa. Lead concentrations ranging from 4.5–46.5 µg/g have been recorded in sediments of the Mandovi Estuary , whereas mangrove sediments along the Chapora and Mandovi Rivers revealed 7.9–50.5 µg/g of lead .…”
Section: Discussionmentioning
confidence: 99%
“…Isolating the bacteria with necessary performance for degradation of organic pollutants such as xylene, anthracene and pyrene in soil and water ecosystems can be the perfect solution for improving the microbial population in areas contaminated by hydrocarbons [5]. Several species of bacterial genera Pseudomonas, Serratia, Marinobacter, Providencia, Alcaligenes, Salmonella, Nocardia, Mycobacterium, Cunninghamella, Rhodococcus, Beijerinckia, Lysinibacillus, Corynebacterium, Diaphorobacter, Pseudoxanthomonas, Bacillus and Sphingomona s; have been found highly capable of degrading petroleum hydrocarbons as well as heavy metals are well documented [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Mercury resistant microorganisms have been isolated from natural waters (Jonas et al, 1984;Barkay, 1987;Schaefer et al, 2004), soils (Diels and Mergeay, 1990;Aleem et al, 2003) and clinical environments (Meissner and Falkinham, 1986). Bacterial mercury resistance has been observed in several pseudomonads, and mercury-tolerant pseudomonads have been suggested be potential environmental bioremediators (Jaysankar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%